Energy and economic growth in Peru: A long-term perspective through cointegration - Caparó, Rafael (2023)
Thinking about the economic growth of a nation is thinking about a series of alternatives. This research article examines the relationship between energy consumption and economic growth in Peru using cointegration models to present development alternatives. The main objective is to analyze the influence of energy consumption on long-term economic growth. To achieve this, a methodology is used that begins with the Unit Root tests and data is collected between 2005 and 2018. The results obtained reveal a significant positive relationship between energy consumption and economic growth in the long term, which indicates that an increase in energy consumption has a positive impact on economic growth. These findings reveal the importance of considering additional and structural factors that influence long-term economic growth. In conclusion, this study contributes to the understanding of the dynamics between energy consumption and economic growth, providing relevant information for policy makers and decision makers in the search for sustainable development.